Whole genome sequencing of Malaysian colorectal cancer patients reveals specific druggable somatic mutations - Mohd Yunos, Ryia Illani; Ab Mutalib, Nurul-Syakima; Khoo, Jia-shiun; Saidin, Sazuita; Ishak, Muhiddin; Syafruddin, Saiful Effendi; Tieng, Francis Yew Fu; Md Yusof, Najwa Farhah; Abd Razak, Mohd Ridhwan; Mahamad Nadzir, Norshahidah; Abu, Nadiah; Rose, Isa Md; et al. (Frontiers in Molecular Biosciences, 2023)
The incidence of colorectal cancer (CRC) is increasing continuously in some areas of the world, including Malaysia. In this study, we aimed to characterize the landscape of somatic mutations using the whole-genome sequencing approach and identify druggable somatic mutations specif-ic to Malaysian patients. Whole-genome sequencing was performed on the genomic DNA ob-tained from tissues of our cohort of 50 Malaysian CRC patients. We discovered five top signifi-cantly mutated genes which are APC, TP53, KRAS, TCF7L2 and ACVR2A. Five novel, non-synonymous variants were identified in our patients involving four genes; KDM4E, MUC16, POTED and KRTAP10-4. At least one druggable somatic alteration was identified in 88% of our patients. Among them were two RNF43 variants which were predicted to have responsive effects against the Wnt pathway inhibitor. The CRC cell line expressing the RNF43 mutations showed increased cell proliferation, increased sensitivity against LGK974 drug treatment and G1 cell cycle arrest. In conclusion, this study uncovered the genomic landscape of our local CRC pa-tients and highlighted the potential of an alternative treatment targeting Wnt/Beta Catenin sig-nalling pathway which could be beneficial especially to Malaysian CRC patients.